Case study on ventilation and cooling control technology of multi heat source coupling in long distance subsea tunnel construction. (August 2021) - Wang, Yapeng
Abstract: To solve the high-temperature environmental hazards caused by concrete hydration heat release in tunnel construction, this paper studies the heat generation mechanism of heat source in the tunnel using theoretical analysis and numerical simulation, and analyzes the temperature control in the tunnel under different ventilation wind speed (1 m/s, 2 m/s, 3 m/s, 4 m/s, 5 m/s) and ventilation temperature (298 K, 293 K, 288 K, 283 K, 278 K). The results show that: increasing the ventilation speed can effectively reduce the environmental temperature in the tunnel, and the ventilation cooling effect is the best when the air duct outlet speed is 3 m/s. Reducing the ventilation temperature can further reduce the tunnel temperature based on increasing the ventilation speed. When the ventilation temperature is set at 293 K, it can meet the needs of ventilation and cooling at the tunnel face. The simulation results show that when the tunnel ventilation speed is 3 m/s and the ventilation temperature is 293 k, the maximum cooling value of the working face can reach 6.66 k, and the maximum cooling rate is 2.18%. Within 5 m from the tunnel working face, the cooling effect of the enclosure structure is the most obvious, which can effectively ensure the comfort of the working environment.